Comparative Analysis of the “Processuality” of the Idea of Civil Society in Europe and Azerbaijan - Dilara Muslimzadeh (Проблеми на постмодерността, 2019)
The article is devoted to the study of the institution of civil society. The article analyzes the role of the civil society institution and provides a broad analysis of this institution in Europe and Azerbaijan.